Photosynthesis : Photobiochemistry and Photobiophysics: VOL.10 - Kê, Bacon (Kluwer Academic Publishers, 2001)
In discussing the structure and function of various protein complexes, we begin with an introductory chapter, followed by chapters on light-harvesting complexes, the primary electron donors and the primary electron acceptors, and finally the secondary electron donors.